Charles H. Houston : an interdisciplinary study of civil rights leadership - Houston, Charles Hamilton, 1895-1950 (Lexington Books, 2012)
"This edited collection focuses on the philosophical ideas, constructive engagement, and lasting contributions of Charles H. Houston, a legal scholar activist who played an important role in the civil rights movement"--